Demulsification of water/sunflower oil emulsions by a tangential filtration process using chemically impregnated ceramic tubes - Del Colle, R.; Longo, Elson [UNESP]; Fontes, S. R. (Elsevier B.V., 2007)
A tangential filtration process was implemented in this study using porous ceramic tubes made of alpha-alumina produced by the slip-casting technique. These tubes were sintered at 1450 degrees C and characterized by mercury intrusion porosimetry, which revealed a mean pore size of 0.5 mu m. The tubes were chemically impregnated with a zirconium citrate solution, after which they were calcined and heat treated at temperatures of up to 600 and 900 degrees C to eliminate volatile organic compounds and transform the zirconium citrate into zirconium oxide impregnated in the alumina in the form of nanoparticle agglomerates. The microporous pipes were tested on a microfiltration hydraulic system to analyze their performance in the demulsification of sunflower oil and water mixtures. The fluid-dynamic parameters of Reynolds number and transmembrane pressure were varied in the process. The volume of permeate was analyzed by measuring the Total Organic Carbon concentration (TOC), which indicated 99% of oil phase retention. The emulsified mixture was characterized by optical microscopy, while the morphology and composition of the impregnated microporous tubes were analyzed by scanning electron microscopy (SEM). Quantification of the TOC values for the tube impregnated once at 600 degrees C showed the best demulsification performance, with the concentration on permeate smaller than 10 mg/L. The impregnated tube sintered once at 900 degrees C presented low carbon concentration (smaller than 20 mg/L), has the advantage of presenting the greatest trans-membrane flux in relation to the other microporous tube. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: microfiltration; emulsions; porous tubes; impregnation; zirconia